Answers

The Brainliest Answer!
2014-12-26T11:17:16+05:30
√2 x² +7x +5 √2 = 0
⇒ √2 x² + 5x + 2x + 5√2 = 0
⇒ √2x²  + 5x + √2*√2*x + 5√2=0
⇒ x(√2x + 5) + √2(√2x + 5) =0
⇒ (x+√2)(√2x+5) = 0
That gives x= - √2 or  x= - 5/√2
2 5 2
PLEASE MARK AS...... BEST.............
the option is not seen...:(
how did u get the third step??
2014-12-26T13:26:33+05:30
√2 x² +7x +5 √2 = 0⇒ √2 x² + 5x + 2x + 5√2 = 0⇒ √2x²  + 5x + √2*√2*x + 5√2=0⇒ x(√2x + 5) + √2(√2x + 5) =0⇒ (x+√2)(√2x+5) = 0That gives x= - √2 or  x= - 5/√2

1 4 1